Optimization of CO2 Absorption Characteristic under the Influence of SO2 in Flue Gas by Hollow Fiber Membrane Contactor - Ziyi Qu; Li Zhang; Yunfei Yan; Shunxiang Ju (Journal of Chemistry)
Hollow fiber membrane contactor is a new, highly efficient, and the most promising technology for CO2 absorption in flue gas. There is still SO2 that exists in the flue gas after desulfurization tower of power plant. This paper studied the influence of SO2 on CO2 absorption characteristic in flue gas by hollow fiber membrane contactor with absorbent of EDA, EDA + MEA (0.6 : 0.4), and EDA + MEA + PZ (0.4 : 0.4 : 0.2). The influences of SO2 concentration, cycle absorption and desorption characteristic of absorbent, absorbent concentration, and liquid-gas flow rate ratio are studied to analyze the influence of SO2 on CO2 absorption characteristic. The appropriate absorbent composition ratio and appropriate parameter range that can inhibit the influence of SO2 are proposed by studying the hybrid sorbent with activating agent, appropriate absorbent concentration, and ratio of liquid-gas flow rate. Among the three kinds of absorbents, EDA + MEA + PZ (0.4 : 0.4 : 0.2) had the best tolerance ability to SO2 and the highest efficiency. With comprehensive consideration of CO2 removal efficiency and operating cost, under the condition of 1000 ppm SO2, the appropriate concentration and liquid-gas flow rate ratio of EDA, EDA + MEA, and EDA + MEA + PZ are proposed.